2015
DOI: 10.1017/s0960258514000403
|View full text |Cite
|
Sign up to set email alerts
|

Physical dormancy in a changing climate

Abstract: Species with physically dormant (PY) seeds make up over 25% of plant species in a number of ecologically important ecosystems around the globe, such as savannah and Mediterranean shrublands. Many of these ecosystems are subject to temporally stochastic events, such as fire and drought; but are in areas projected to experience some of the most extreme climatic changes in the future. Given the importance of PY in controlling germination timing for successful recruitment, we ask how plastic the PY trait is, and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
85
1
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 85 publications
(94 citation statements)
references
References 105 publications
(192 reference statements)
4
85
1
2
Order By: Relevance
“…Nonetheless, a recent study focussing on five Fabaceae woody species found significant intra-population differences in initial dormancy only in one of the species (Liyanage & Ooi 2015). Intra-population variability could be a strategy that buffers species against local unpredictable events such as fire and drought (Hudson et al 2015;Liyanage & Ooi 2015) allowing a staggered seed germination.…”
mentioning
confidence: 98%
See 4 more Smart Citations
“…Nonetheless, a recent study focussing on five Fabaceae woody species found significant intra-population differences in initial dormancy only in one of the species (Liyanage & Ooi 2015). Intra-population variability could be a strategy that buffers species against local unpredictable events such as fire and drought (Hudson et al 2015;Liyanage & Ooi 2015) allowing a staggered seed germination.…”
mentioning
confidence: 98%
“…Furthermore, some studies have suggested that PY variability allows seeds to persist in variable environments (Ooi et al 2012;Fernández-Pascual et al 2013). However, there is scarce knowledge about the degree of PY variability, both among and within populations, especially in natural ecosystems (Cochrane et al 2015;Hudson et al 2015).…”
mentioning
confidence: 99%
See 3 more Smart Citations